Analysis of Sigmund Freud’s Views on the Origin ofreligion in His Totem and Taboo - Mustafayeva, Gunel (Scholarya Demo Journal of Ruby, 2019)
Being the founder of psychoanalysis, Sigmund Freud left a deep mark on thehistory of psychology. He introduced pioneering ideas in the study of humanmind. The article analyzes Sigmund Freud’s ideas on religion, its origins, human psychology and the position of religion in the life of society. Thus, its research object is psychoanalysis and religion, founded and developed by S.Freud. The article utilizes the sources dealing with Freud’s way of life, his innovations in psychology as well as the sources covering the theory of religion for a deeper analysis of the subject. His religious views are reflected in many of his works, including Totem and Taboo. In this sense, Totem and Taboo has been chosen as a research object for a particular reason. Although over a hundred years have elapsed, Totem and Taboo is still considered one of the classic books of psychoanalysis. Freud sought to explore the origins of human society, culture and civilization, based on his own psychoanalytic theory, and created his own new theory of moral, religious and legal norms. The main purpose of the article is not to expose the accuracy or incorrectness of these ideas, but rather to see Freud’s relationship with religion and psychoanalysis. To that end, the article attempted to objectively and fully analyze S.Freud’s psychoanalytic theory.